Exploring the Mechanism of Yougui Pill against Aging Based on Network Pharmacology and Molecular Docking Study - Yang, Haiyan; Shi, Qian; Ji, Chunchun (Chinese medicine and natural products, 2025)
This study aimed to explore the mechanism of obtaining yang from yin in Yougui pill against aging based on network pharmacology and molecular docking technology.The active components and targets of Yougui Pill were obtained by searching the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) database and the Bioinformatics Analysis Tool for Molecular mechANism of Traditional Chinese Medicine (BATMEN-TCM) database, and kidney deficiency syndrome-related targets were obtained in the Symptom Mapping (SymMap) Database, a traditional Chinese medicine (TCM) syndrome correlation database. The protein–protein interaction (PPI) network was constructed by using the STRING11.5 database. Then, we used CytoScape3.9.0 software to construct the network of TCM–active components–potential targets, and the core TCM components and core targets of Yougui Pill for the treatment of kidney deficiency were obtained. The function analysis of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) signaling pathway enrichment analysis were performed in the Database for Annotation, Visualization, and Integrated Discovery (DAVID). Finally, preliminary verification was performed with the help of molecular docking technology.A total of 147 active components of 9 drugs of Yougui Pill (Fuzi [Aconiti Lateralis Radix Praeparata], Shudihaung [Rehmanniae Radix Praeparata], Gouqi [Lycii Fructus], Shanyao [Rhizoma Dioscoreae], Shanzhuyu [Corni Fructus], Tusizi [Cuscutae Semen], Danggui [Angelicae Sinensis Radix], Duzhong [Eucommiae Cortex], Lujiaojiao [Cervi Cornus Colla]) were obtained, corresponding to 233 targets. A total of 2,235 targets related to kidney deficiency syndrome and 43 potential therapeutic targets were obtained after the intersection. The core TCM components mainly included quercetin, kaempferol, diosgenin, β-carotene, etc. The core targets involved Trp53 (Tp53), Akt1, Pparg, Nr3c1, App, Casp8, Mapk1, Cav1, and Ctnnb1. A total of 27 biological processes, 10 cellular components, and 11 molecular functions were obtained by gene function enrichment analysis, mainly related to the regulation of gene expression, cell apoptosis and proliferation, and the response to estrogen. A total of 51 KEGG signaling pathways, mainly involving a variety of cancer pathways, apoptosis pathways, longevity regulation pathways, etc.Yougui Pill can play a role in preventing and treating kidney deficiency syndrome through multiple targets and pathways.
Keywords: Yougui Pill; aging; kidney deficiency syndrome; obtaining Yang from Yin; network pharmacology; molecular docking